Hobbes to Rousseau : Inequality, Institutions, and Development - Matteo Cervellati; Piergiuseppe Fortunato; Uwe Sunde (Institute for the Study of Labor (IZA), 2005)
We analyze the endogenous evolution of economic and political institutions and the interdependencies with the process of economic development. Favorable economic institutions ensure the appropriability of rents in form of a state of law. We study the conditions under which a state of law can be implemented under oligarchy, and when democratization is necessary. Inequality in endowments and incomes prolongs the absence of good institutions and delays democratization. Conversely, institutions shape the income distribution. Simulations illustrate how inequality affects the development process and may lead to overtaking and divergence. The implications are in line with historical and empirical evidence.
Keywords: N10; O20; H10; 330; inequality; democratization; institutions; state of law; long-term development; Institutioneller Wandel; Entwicklung; Rechtsstaat; Einkommensverteilung; Demokratisierung; Verfassungsökonomik; Public Choice; Theorie